Social avalanche : crowds, cities and financial markets - Borch, Christian (Cambridge, United Kingdom : Cambridge University Press, 2020)
'Individuality and collectivity are at the heart of sociological inquiry. Through a tour de force of cultural history, social theory, urban sociology and economic sociology, Christian Borch offers an innovative rethinking of these terms and their interconnections via the concept of the social avalanche. Drawing on classical sociology, he argues that while individuality embodies a tension between collective mimetic forces and anti-mimetic autonomy, certain situations, such as crowds and moments of collective behaviour, can subsume the individual entirely within the collective. These events, or social avalanches, produce an experience of being swept away suddenly and losing one's sense of self. Cities are often on the verge of social avalanches, their urban inhabitants torn between de-individualising external pressure and autonomous self presentation, and Borch explores the role of tensional individuality and social avalanches within them. Similarly, present-day financial markets, dominated by computerised trading, abound with social avalanches and the tensional interplay of mimesis and autonomous decision-making - although it is not humans but fully automated algorithms that avalanche there'--
Includes bibliographical references and index.
Keywords: Social change; Individualism; Collective behavior; Economics -- Sociological aspects; Sociology, Urban